2021
DOI: 10.3389/fenvs.2021.635365
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Above-Ground Carbon-Stocks for Urban Greeneries in Arid Areas: Case Study for Doha and FIFA World Cup Qatar 2022

Abstract: Urban areas are significant sources of anthropogenic carbon dioxide (CO2), which elevates air pollution. However, urban greenery has a positive effect on mitigating air pollution and the impact of CO2 on the climate. Quantifying the benefits of greenery for urban environments involves complex calculations and requires significant resources. Such a quantifying exercise is not cost-effective. The satellite remote sensing method can analyze current and near-present carbon-stock dynamics through spectral band imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…A study of organic versus conventional farming revealed that conventional farming was associated with higher relative abundance of Actinobacteria ( 37 ), as we observed in our farm sample. Urban parks in Qatar bear some similarity to farms in that they are intensively managed with an abundance of fertilizers, which possibly explains the abundance of Actinobacteria in parks ( 38 ). Urban parks in western China are also dominated by Actinobacteria ( 39 ), possibly due to higher microbial biomass nitrogen, which correlated with nitrogen and organic matter availability ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study of organic versus conventional farming revealed that conventional farming was associated with higher relative abundance of Actinobacteria ( 37 ), as we observed in our farm sample. Urban parks in Qatar bear some similarity to farms in that they are intensively managed with an abundance of fertilizers, which possibly explains the abundance of Actinobacteria in parks ( 38 ). Urban parks in western China are also dominated by Actinobacteria ( 39 ), possibly due to higher microbial biomass nitrogen, which correlated with nitrogen and organic matter availability ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is because the carbon liability may take decades to neutralize. Standardization of carbon accounting techniques and measurement of above‐ground carbon stocks can help to keep track of the sink performance of urban green spaces 113,120 …”
Section: Methodsmentioning
confidence: 99%
“…Above-ground biomass (AGB) of vegetation is an important indicator for measuring the carbon sequestration capacity of a region and assessing its carbon balance [1][2][3]. Because vegetation fixes atmospheric CO 2 in the form of carbohydrates in urban ecosystems through photosynthesis [4], this carbon sequestration capacity is closely related to the AGB of vegetation. Moreover, carbon stocks can also be obtained by calculating the AGB of vegetation in the region [5,6].…”
Section: Introductionmentioning
confidence: 99%